Suppression of B‐cell activation and IgE, IgA, IgG1 and IgG4 production by mammalian telomeric oligonucleotides. Issue 5 (9th March 2013) - Sackesen, C.; van de, W.; Akdis, M.; Soyer, O.; Zumkehr, J.; Ruckert, B.; Stanic, B.; Kalaycı, O.; Alkan, S. S.; Gursel, I.; Akdis, C. A.
Abstract Background The fine balance of immunoglobulins (Ig) E, IgG1, IgG4 and IgA in healthy production is maintained by the interaction of B cells with adaptive and innate immune response. The regulation of toll‐like receptors (TLRs)‐driven innate and adaptive immune effector B‐cell response and the role of mammalian telomeric TTAGGG repeat elements represent an important research area. Methods Human PBMC and purified naive and memory B cells were stimulated with specific ligands for TLR2, TLR3, TLR4, TLR5, TLR7, TLR8 and TLR9 in the presence or absence of telomeric oligonucleotides. B‐cell proliferation, differentiation and antibody production were determined. Results TLR9 ligand directly activates naive and memory B cells, whereas TLR7 can stimulate them in the presence of plasmacytoid dendritic cells. Human B cells proliferate and turn into antibody‐secreting cells in response to TLR3, TLR7 and TLR9, but not to TLR2, TLR4, TLR5 and TLR8 ligands. Stimulation of B cells with intracellular TLR3, TLR7 and TLR9 induced an activation cascade leading to memory B‐cell generation and particularly IgG1, but also IgA, IgG4 and very low levels of IgE production. Mammalian telomeric oligodeoxynucleotide (ODN) significantly inhibited all features of TLR ligand‐induced events in B cells including B‐cell proliferation, IgE, IgG1, IgG4, IgA production, class switch recombination, plasma cell differentiation induced by TLR3, TLR7 and TLR9 ligands. Conclusion B cells require specific TLR stimulation, T‐cell and plasmacytoid dendritic cell help for distinct activation and Ig production profiles. Host‐derived telomeric ODN suppress B‐cell activation and antibody production demonstrating a natural mechanism for the control of overexuberant B‐cell activation, antibody production and generation of memory.